(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this article, in a bigeneralized topological space, we introduce a new space namely, (s, v)-bigeneralized submaximal space, and analyze its nature. Also, the characterization theorem for a (s, v)-bigeneralized submaximal space, image and preimage of (s, v) bigeneralized submaximal is a (s, v)-bigeneralized submaximal space under (µ, η)-open, (µ, η)-continuous map, respectively are proved. Further, the relationship between hyperconnected space and submaximal space in a pairwise bigeneralized submaximal space is given.